Exploration of the Work Engagement of Millennial Generation: A Perspective on Job Characteristics - Wada, Wardatul; Rahmah, Dian Dwi Nur (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The millennial generation possesses a spirit of optimism and high loyalty within the company; however, millennials tend to prefer seeking alternative employment opportunities that offer room for growth, commonly referred to as turnover. One influencing factor in this phenomenon is the work engagement of employees and job characteristics. This study aims to determine the relationship between job characteristics and work engagement among millennial generation employees. This research method uses a quantitative approach. The subjects of this study were 250 millennial generation employees who were selected using a purposive sampling technique. The data collection method used is the work engagement scale and the job characteristics scale. The data analysis used is the Kendall Tau correlation test. The results showed that the value of p = 0.000 (p <0.05) and a correlation value of 0.318, which means that there is a positive and significant relationship between work characteristics and work engagement among millennial generation employees. The implication based on the results of the research is that job characteristics have an important role to play in increasing employee engagement, by giving freedom to employees in handling work and opportunities to contribute to the company.Generasi milenial memiliki jiwa optimisme dan loyalitas yang tinggi dalam perusahaan, namun nyatanya generasi milenial lebih memilih mencari pekerjaan lain yang memiliki kesempatan untuk berkembang atau disebut turnover. Salah satu faktor yang memengaruhi hal ini adalah keterikatan kerja karyawan dan karakteristik pekerjaan. Penelitian ini bertujuan untuk mengetahui hubungan karakteristik pekerjaan dengan keterikatan kerja pada karyawan generasi milenial. Metode penelitian ini menggunakan pendekatan kuantitatif. Subjek penelitian ini berjumlah 250 karyawan generasi milenial yang dipilih dengan menggunakan teknik purposive sampling. Metode pengumpulan data yang digunakan adalah dengan skala keterikatan kerja dan skala karakteristik pekerjaan. Analisis data yang digunakan adalah uji korelasi kendall tau. Hasil pada penelitian menunjukkan bahwa nilai p = 0.000 (p < 0.05) dan nilai korelasi sebesar 0.318 yang artinya terdapat hubungan positif dan signifikan karakteristik pekerjaan dengan keterikatan kerja pada karyawan generasi milenial. Implikasi berdasarkan pada hasil penelitian adalah karakteristik pekerjaan memiliki peran penting untuk meningkatkan keterikatan kerja karyawan, dengan memberi kebebasan pada karyawan dalam menangani pekerjaan dan kesempatan untuk memberikan kontribusi pada perusahaan.